Designing Multi-Dopant Species in Microporous Architectures to Probe Reaction Pathways in Solid-Acid Catalysis - Potter, Matthew E.; Armstrong, Lindsay-Marie; Carravetta, Marina; Mezza, Thomas M.; Raja, Robert (Frontiers in Chemistry, 2020)
The introduction of two distinct dopants in a microporous zeotype framework can lead to the formation of isolated, or complementary catalytically active sites. Careful selection of dopants and framework topology can facilitate synergistic enhancements in catalysts efficiency in a range of reaction pathways, leading to the use of sustainable precursors (bioethanol) for plastic production. In this work we describe our unique synthetic design procedure for creating a bimetallic solid-acid catalyst (MgSiAPO-34), designed to improve and contrast with the performance of SiAPO-34 (monometallic analogue), for the dehydration of ethanol to ethylene. We employ a range of in situ characterisation techniques to explore the influence of magnesium substitution, with specific attention to the acidity of the framework. Through a combined catalysis, kinetic analysis and computational fluid dynamics (CFD) study we explore the reaction pathway of the system, with emphasis on the improvements facilitated by the bimetallic MgSiAPO-34 species. The experimental data supports the validation of the CFD results across a range of operating conditions; both of which supports our hypothesis that the presence of the bimetallic solid acid centres enhances the catalytic performance. Furthermore, the development of a robust computational model, capable of exploring chemical catalytic flows within a reactor system, affords further avenues for enhancing reactor engineering and process optimisation, towards improved ethylene yields, under mild conditions.